Annona Muricata reduced Hepatocytes Differentiation Caused by Cycas revoluta in Wistar Rats - AHOKPE, ANGÈLE MÉLANIE (My University, 2019)
Our study aims to evaluate the action of Annona muricata ethyl extract in the traditional treatment of liver cancer in Wistar rats. This is an analytical, prospective and control study that took place at the Laboratory of Biomembrans and Cell Signaling of the University of Abomey Calavi. The objective of this study is to verify the effects of the ethyl extracts of Annona muricata leaves on the differentiation of hepatocytes in the Wistar rat. For this, an ethyl extraction was carried out using the dried leaf powder of Annona muricata and ethanol at 90°, as well as the extraction of the leaves of Cycas revoluta. Cycas revoluta-induced differentiation-lowering activity was assessed by assaying the total protein and alkaline phosphatase (PAL) parameters on a Wistar rat liver mash supernatant in which hepatocyte differentiation had previously been induced by exposure to the powder and ethyl extract of Cycas revoluta by gavage. Our sample included 3 batches of Wistar rats. Batch 1 was the control batch, batchs 2 and 3, respectively exposed to the powder and the extract of Cycas revoluta for 2 weeks, then subjected to gavage 100 mg / kg of extracts of Annona muricata for 2 more weeks. At the end of our study it was revealed that the activity of PAL and the total protein content which was high following exposure to Cycas revoluta, was significantly reduced after the treatment with ethyl extracts of Annona muricata leaves. In addition, it was also the ratio PAL / total protein that accounts for the stage of differentiation, which was increasing under the effect of Cycas revoluta, decreased after administration of the ethyl extracts of the leaves of Annona muricata. These results make it possible to demonstrate the action of Annona muricata extracts on the differentiation of Wistar rat liver cells induced by a carcinogenic substance such as powder and extract of Cycas revoluta.
Keywords: Annona muricata; Cycas revoluta; hepatocytes; extract; differentiation